PEMBERDAYAAN KELOMPOK TP-PKK DESA ARGO MULYO, KECAMATAN SEPAKU, PENAJAM PASER UTARA MELALUI POJOK LITERASI TANAMAN OBAT KELUARGA (TOGA) - Rozi, Fahrul; Siddiq, Muhammad Nuzul Azhim Ash; Anggreini, Putri; Kawareng, Andi Tenri; Wahyuni, Leny Eka Tyas; Nisaa, Nur Rezky Khairun; Majiding, Chaidir Masyhuri; Annisa, Oktavia Nasrul; Putra, Arya Yuliansyah; Aulia, Nasywa; Febriyanthy, Adhiesty Syaffila (Universitas Mataram, 2024)
Hypertension and hypercholesterolemia are common health problems in Argo Mulyo Village, Sepaku Sub-district, North Penajam Paser Regency. These diseases require a preventive approach through the utilization of family medicinal plants (TOGA) such as ginger, turmeric, and temulawak, which have been proven effective in reducing blood pressure and cholesterol levels. This empowerment activity aims to increase community knowledge, particularly among the TP-PKK group, regarding the use of TOGA as a preventive measure against hypertension and hypercholesterolemia. The activity was conducted on September 7-8, 2024, in Argo Mulyo Village. The methods used included education, training on the production of herbal powder from ginger, turmeric, and temulawak, and the planting of TOGA in the village land. Evaluation was carried out through pretest and posttest assessments to measure the participants' knowledge improvement. The results of the educational activity related to hypertension and hypercholesterolemia showed a significant increase in participants' knowledge, with an average pretest score of 60.23 rising to 76.51 in the posttest. The results of the herbal powder-making activity also showed an improvement in knowledge, with the pretest average score at 71.76 and 92.94 in the posttest. Additionally, the herbal powder products produced by the participants met the established standards. The planting of TOGA in the village land was also successfully implemented, indicating the success of this activity in raising community awareness and skills in utilizing local resources. In conclusion, this TOGA-based empowerment not only contributes to improving community health but also holds the potential to enhance economic welfare through herbal production.